Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening: (Study Pada Karyawan PT. Bank Rakyat Indonesia Tbk. Pontianak Cabang Gajah Mada) - Feriansyah, Feriansyah; Sapala, Silpanus Dian; Purnomo, Eddy; Zulimi, Zulimi (Jurnal Ekonomi STIEP, 2025)
The purpose of this study was to determine and analyze the effect of transactional leadership style and transformational leadership style on employee performance through work motivation as an intervening variable. This research is a survey research, which uses an explanatory research type, which provides an explanation of the causal relationship between variables through hypothesis testing. The sampling technique in this study using purposive sampling technique, the sample used amounted to 47 respondents. The research method uses path analysis using SPSS 24 software. Data were analyzed using instrument tests and path analysis. The results showed that each variable had a significant effect even though the effect was not too large. Partially Transactional leadership style (X1) has a significant influence on employee performance (Y). Partially Transformational leadership style (X2) has a significant influence on employee performance (Y). Partially, work motivation (Z) has a significant effect on employee performance (Y).Partially Transactional Leadership style (X1) has a significant effect on Work Motivation (Z). Partially, the Transformational Leadership style (X1) has a significant influence on work motivation (Z). Partially the Transactional Leadership style (X2 has a significant influence on employee performance (Y) through work motivation (Z). Partially, the Transformational Leadership style (X2) has a significant influence on employee performance (Y) through work motivation (Z)